MARAKNYA KASUS PERCERAIAN AKIBAT DARI PERKAWINAN DI BAWAH UMUR (Studi Kasus Pengadilan Agama Banyuwangi) - Erisa Agus Tiana Umi Saputri; Ratna Artha Windari; Adnyani, Ni Ketut Sari (Jurnal Ilmu Hukum Sui Generis, 2025)
This research aims to provide knowledge or information regarding the influence of divorce caused by underage marriage. The high rate of underage marriage shows that empowerment regarding regulations imposed by the government is still low. Apart from that, several supporting factors such as education, economics, social and culture cause someone to marry underage. From a psychological perspective, the emotional condition of couples who are not old enough and who are considered unstable has an impact on arguments that end in divorce. Apart from divorce, young married couples will also experience a fairly high risk of maternal and infant mortality. The method used in this research is empirical legal research with a descriptive approach. Data was collected through observation, interviews and document study, with a sample selection consisting of underage marriage perpetrators who ended up filing for divorce at the Banyuwangi Religious Court. The research results show that there is a significant influence on underage marriage and the divorce rate that occurs in Banyuwangi. One of the efforts made by judges to limit the divorce rate is through intensifying the use of mediation for couples who file for divorce